Non-Gaussian diffusion MRI of gray matter is associated with cognitive impairment in multiple sclerosis. (June 2015) - Bester, M; Jensen, JH; Babb, JS; Tabesh, A; Miles, L; Herbert, J; Grossman, RI; Inglese, M
Background: Non-Gaussian diffusion imaging by using diffusional kurtosis imaging (DKI) allows assessment of isotropic tissue as of gray matter (GM), an important limitation of diffusion tensor imaging (DTI). Objective: In this study, we describe DKI and DTI metrics of GM in multiple sclerosis (MS) patients and their association with cognitive deficits. Methods: Thirty-four patients with relapsing–remitting MS and 17 controls underwent MRI on a 3T scanner including a sequence for DKI with 30 diffusion directions and 3b values for each direction. Mean kurtosis (MK), mean diffusivity and fractional anisotropy (FA) of cortical and subcortical GM were measured using histogram analysis. Spearman rank correlations were used to characterize associations among imaging measures and clinical/neuropsychological scores. Results: In cortical GM, a significant decrease of MK (0.68 vs. 0.73; p < 0.001) and increase of FA (0.16 vs. 0.13; p < 0.001) was found in patients compared to controls. Decreased cortical MK was correlated with poor performance on the Delis-Kaplan Executive Function System test ( r = 0.66, p = 0.01). Conclusion: Mean kurtosis is sensitive to abnormality in GM of MS patients and can provide information that is complementary to that of conventional DTI-derived metrics. The association between MK and cognitive deficits suggests that DKI might serve as a clinically relevant biomarker for cortical injury.